Lubrication of rail by traction unit in the train - V. S. Kossov; A. A. Lunin; Yu. A. Panin; A. V. Trifonov; I. E. Il'in (Вестник Научно-исследовательского института железнодорожного транспорта)
Interaction of rolling stock and track is a fundamental physical process while running cars, locomotives and trains on the railway. The Research, Design and Technological Institute of the rolling stock (JSC "VNIKTI") for more than twenty years conducting research to reduce cost of energy for traction.The Institute has developed rail lubrication technology performed by locomotive leading the train, but with the improvement: the lubrication of the internal rolling surface of the rail in curve performed by leading locomotive and on sections where lubrication made on side surface of the head of the outer rail - by lubricating cars. This technology can reduce the side impact of the rolling stock on the railway track in curved sections, to reduce resistance to motion while maintaining the length of the braking distance. The effect of reducing the side impact to the track is achieved by reducing the coefficient of friction on the rolling surface of the inner rail and the side surface of the outer rail, which leads to a proportional reduction of transverse forces of creep. Such reduction of transverse forces in creep decreases the normal reaction at the flange of the oncoming wheel and, consequently, reduces motion resistance (reduction in energy consumption for traction), reduce wear, both wheel flanges of rolling stock and rails in curves.Lubrication of rail by traction unit in the train has a broad perspective of application on the railway network of JSC "Russian Railways". The minimum cost of additional equipping locomotives with devices automatically applying friction modifiers and manufacture of friction modifiers will payback considerable profit by savings of traction resources and by savings associated with a reduction in regrinding of wheelsets and replacement of rails in curves.